Effective Dosage of Oral Vancomycin in Treatment for Initial Episode of Clostridioides difficile Infection: A Systematic Review and Meta-Analysis - Chia-Yu Chiu; Amara Sarwal; Addi Feinstein; Karen Hennessey (MDPI AG, 2019)
Background: Oral vancomycin is a first line treatment for an initial episode of Clostridioides difficile infection. However, the comparative efficacy of different dosing regimens is lacking evidence in the current literature. Methods: We searched PubMed, Embase, Cochrane Library, and ClinicalTrials.gov. from inception to May 2019. Only articles published in English are reviewed. This meta-analysis compares the effects of low dose oral vancomycin (<2 g per day) versus high dose vancomycin (2 g per day) for treatment of initial Clostridioides difficile infection. Results: One randomized controlled trial and two retrospective cohort studies are included. A total of 137 patients are identified, 53 of which were treated with low dose oral vancomycin (39%) and 84 with high dose oral vancomycin (61%). There is no significant reduction in recurrence rates with high dose vancomycin compared to low dose vancomycin for treating initial episodes of non-fulminant Clostridioides difficile infection ((odds ratio (OR) 2.058, 95%, confidence interval (CI): 0.653 to 6.489). Conclusions: Based on limited data in the literature, low dose vancomycin is no different than high dose vancomycin for treatment of an initial episode of Clostridioides difficile infection in terms of recurrence rate. Additional large clinical trials comparing the different dosages of vancomycin in initial Clostridioides difficile infection are warranted.